1997
DOI: 10.1177/004051759706701004
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for Dye Diffusion in Wool Fibers

Abstract: The most prominent view of the diffusion mechanism of dyes into wool fibers assumes that the molecules primarily enter the fiber in a fast process along the cell membrane complex (CMC), that is, by an intercellular mechanism. From the CMC, they are subsequently distributed in a slower process throughout the other morphological components according to their respective diffusion coefficients and dye affinities. This view, referred to here as the CMC-diffusion model, is based on investigations of the diffusion pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 13 publications
2
46
0
Order By: Relevance
“…A 5-min exposure of hair to an aqueous solution containing 1 mg/L cocaine hydrochloride was sufficient to produce measurable cocaine concentrations of 0.2 g/g of hair (34 ). From experiments involving dyestuffs (35)(36)(37) and drugs such as opiates (38 ), it can be assumed that, in intact hair, diffusion via the cuticle cell edges along the endocuticle and the cell membrane complex proceeds rapidly. From there, solutes are probably further distributed throughout the other morphologic components of hair by a slower process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 5-min exposure of hair to an aqueous solution containing 1 mg/L cocaine hydrochloride was sufficient to produce measurable cocaine concentrations of 0.2 g/g of hair (34 ). From experiments involving dyestuffs (35)(36)(37) and drugs such as opiates (38 ), it can be assumed that, in intact hair, diffusion via the cuticle cell edges along the endocuticle and the cell membrane complex proceeds rapidly. From there, solutes are probably further distributed throughout the other morphologic components of hair by a slower process.…”
Section: Discussionmentioning
confidence: 99%
“…From experiments on diffusion of dyestuffs and drugs, there is also evidence that adsorption and diffusion of foreign matter is strongly influenced by the hair morphology (35)(36)(37)(38). Scalp hair plays an important role in individual appearance and, therefore, is frequently subjected to cosmetic treatments such as perming or bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lower resolution of the light microscope, compared with the transmission electron microscope, restricts the amount of information that can be obtained by this technique. Wortmann et al (Wortmann et al, 1997) summarized different ideas about this subject. They justified that due to the CMC size in the fiber, intercellular pathway appears questionable.…”
Section: Fig 1 Diffusion Pathways For Dyes Into Woolmentioning
confidence: 99%
“…But only the two latter ones may be assumed to play a role in the intercellular pathway. After a revision of different experiments from several authors (Wortmann et al, 1997) and further references therein, they suggested that there is, in fact, little evidence for the intercellular pathway, which identifies intercellular diffusion as the primary pathway for dyes into fibers. Instead the results support their view that under normal dyeing conditions, diffusion proceeds through the nonkeratinous components of the fiber according to a restricted transcellular diffusion mechanism.…”
Section: Fig 1 Diffusion Pathways For Dyes Into Woolmentioning
confidence: 99%
See 1 more Smart Citation